2007
DOI: 10.1002/hec.1252
|View full text |Cite
|
Sign up to set email alerts
|

Predicting risk selection following major changes in medicare

Abstract: The Medicare Modernization Act of 2003 created several new types of private insurance plans within Medicare, starting in 2006. Some of these plan types previously did not exist in the commercial market and there was great uncertainty about their prospects. In this paper, we show that statistical models and historical data from the Medicare Current Beneficiary Survey can be used to predict the experience of new plan types with reasonable accuracy. This lays the foundation for the analysis of program modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This property, known as the independence of irrelevant alternatives (IIA) can be tested (Greene, 2003) and conditional logit models fail these tests when applied with similar data to the choice of Medicare plans (Atherly et al, 2004;Pizer et al, 2008Pizer et al, , 2009. We follow this literature by selecting a nested logit model to address the rejection of IIA assumptions in the simple conditional logit.…”
Section: Statistical Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…This property, known as the independence of irrelevant alternatives (IIA) can be tested (Greene, 2003) and conditional logit models fail these tests when applied with similar data to the choice of Medicare plans (Atherly et al, 2004;Pizer et al, 2008Pizer et al, , 2009. We follow this literature by selecting a nested logit model to address the rejection of IIA assumptions in the simple conditional logit.…”
Section: Statistical Modelmentioning
confidence: 98%
“…The IIA assumption still applies within nests, but it is more likely to hold if nests have been chosen that group similar choices together. Pizer et al (2008Pizer et al ( , 2009 show that a three-nest structure (HMOs, Medigap plans, and traditional fee-forservice) passes within-nest IIA tests with MCBS data. This nesting structure is illustrated in Fig.…”
Section: Statistical Modelmentioning
confidence: 98%
“…Lagged total drug spending and lagged number of prescriptions are obtained from the prior year's MCBS dataset. We adjusted lagged total drug spending for moral hazard and possible under-reporting as described in Pizer et al (2008). The remainder of this appendix describes the computation of the average copayment for a plan.…”
Section: Resultsmentioning
confidence: 99%
“…This adverse selection problem would force plans to raise premiums repeatedly until most enrollees were driven away. Simulation analyses of the subsidy and coverage structure established by MMA indicated that PDPs will experience adverse selection, but the subsidy is large enough to ensure stability of this plan type (Pizer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation